Legal relationships among the participants and with third parties - Feltham, Ivan (Revue générale de droit, 1988)
“Joint venture” or consortium is studied in this conference in regard to its implications in Canada and abroad. Its legal environment is analysed especially abroad where it involves two jurisdictions, domestic and foreign. In the context of project joint ventures, the relationships of the parties among themselves and with third parties are discussed in some detail. A joint or separate liability is considered. Finally, the essential criteria for a joint venture agreement are presented in order to guide the participants, with a word on business ethics.